Visual conditions and postural directions affect postural sway variability in patients with Parkinson’s disease - Rinaldi, Natalia Madalena; Barbieri, Fabio Augusto [UNESP]; Teixeira-Arroyo, Claudia [UNESP]; Stella, Florindo [UNESP]; Gobbi, Lilian Teresa Bucken [UNESP] (Desafio Singular, Lda, 2015)
Postural sway variability was evaluated in Parkinson’s disease (PD) patients at different stages of disease. Twenty PD patients were grouped into two groups (unilateral, 14; bilateral, 6) according to disease severity. The results showed no significant differences in postural sway variability between the groups (p ≥ 0.05). Postural sway variability was higher in the antero-posterior direction and with the eyes closed. Significant differences between the unilateral and bilateral groups were observed in clinical tests (UPDRS, Berg Balance Scale, and retropulsion test; p ≤ 0.05, all). Postural sway variability was unaffected by disease severity, indicating that neurological mechanisms for postural control still function at advanced stages of disease. Postural sway instability appears to occur in the antero-posterior direction to compensate for the stooped posture. The eyes-closed condition during upright stance appears to be challenging for PD patients because of the associated sensory integration deficit. Finally, objective measures such as postural sway variability may be more reliable than clinical tests to evaluate changes in balance control in PD patients.

Variabilidade de oscilação postural, testes de equilíbrio de Berg e retropulsão foram investigados em pacientes com DP em diferentes estágios da doença. Vinte pacientes com DP participaram deste estudo e foram distribuídos em dois grupos: unilateral (14) e bilateral (6). Os resultados mostraram diferença não significativa entre os grupos para a variabilidade de oscilação postural (p≥0.05). Ainda, a variabilidade de oscilação postural foi maior na direção antero-posterior e na condição de olhos fechados. Para os testes clínicos, UPDRS (seções funcional e motora), teste de Berg e retropulsão, foi encontrada diferença significativa entre os grupos (unilateral e bilateral) (p≤0.05). A partir destes resultados, foi possível concluir que a variabilidade de oscilação postural não muda em função da severidade da doença. Os mecanismos neurológicos para o controle postural ainda estão operando no estágio avançado da doença. Assim, a instabilidade postural parece ocorrer na direção antero-posterior como um mecanismo compensatório em função da postura rígida. A condição de olhos fechados parece ser desafiadora para pacientes com DP, em função dos deficits da integração sensorial. Finalmente, a variabilidade de oscilação postural pode ser considerada uma medida confiável, pois elimina o efeito da subjetividade.
Alterações nas condições visuais pode afetar a variabilidade de oscilação postural em pacientes com Parkinson em diferentes níveis da doença
Keywords: Variability; Postural control; Sensory information; bBlance tests; Variabilidade; Controle postural; Informação sensorial; Testes de equilíbrio